2018
DOI: 10.1029/2017jd028263
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Warm‐Core Structure in Reanalysis and Satellite Data Sets Using HS3 Dropsonde Observations: A Case Study of Hurricane Edouard (2014)

Abstract: Using National Aeronautics and Space Administration Hurricane and Severe Storm Sentinel (HS3)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Schenkel and Hart () showed that some of the reanalysis uses vortex relocation, which in turn responsible for the simulation of the nonphysical life cycle. In contrast, Gao et al () indicated that a vortex relocation/bogusing, assimilation of TC observation data, and model parameterizations are essential to adequately represent warm cores in terms of strength and three‐dimensional structure. Both of these studies indicated the requirements of more observations around the TC core.…”
Section: Introductionmentioning
confidence: 99%
“…Schenkel and Hart () showed that some of the reanalysis uses vortex relocation, which in turn responsible for the simulation of the nonphysical life cycle. In contrast, Gao et al () indicated that a vortex relocation/bogusing, assimilation of TC observation data, and model parameterizations are essential to adequately represent warm cores in terms of strength and three‐dimensional structure. Both of these studies indicated the requirements of more observations around the TC core.…”
Section: Introductionmentioning
confidence: 99%
“…The initial and lateral boundary conditions of the model were obtained from the Global Forecast System Final Analysis (FNL) of the National Centers for Environmental Prediction with horizontal grid spacing of 1° × 1° at 6‐hr interval. Since the TC intensity in the FNL was always weaker than that in observations and often with discrepancy in the position of the TC center (Gao et al, ), a dynamical initialization (DI) scheme was used to spin up the TC. The detailed information of DI can be found in Cha and Wang () and Liu et al ().…”
Section: Model and Experimental Designmentioning
confidence: 99%
“…The FNL data is chosen in this study because it is the most commonly used dataset for synoptic-scale TC studies, e.g., [34,43]. It has been shown to outperform the other modern reanalyses/analyses, such as the NCEP Climate Forecast System Reanalysis (CFSR), the Modern-Era Retrospective analysis for Research and Applications, version 2 (MERRA-2) and the Japanese 55-year Reanalysis (JRA-55), in representing structure and intensity of a hurricane case [44]. FNL may well represent tropical disturbances/depressions due to assimilation of numerous observational data including scatterometer/radiometer winds from QuikSCAT, ASCAT, WindSat, and SSM/I [45], although it underestimates high winds (>17 m s −1 ) under TC conditions [43].…”
Section: Datamentioning
confidence: 99%